ChemInform Abstract: A Practical Guide for Predicting the Stereochemistry of Bifunctional Phosphoric Acid Catalyzed Reactions of Imines. Issue 28 (June 2016) - Reid, Jolene P.; Simon, Luis; Goodman, Jonathan M.
Abstract: Review: 60 refs.